SISTEM PEMINJAMAN BUKU BERBASIS RFID - Purnomo, Yuda Edi, Heru Supriyono, ST. MSc. PhD (2017)
Today's technology is currently experiencing rapid growth. Found many tools that can help resolve human work, one of which is the Radio Frequency Identification (RFID). RFID can be used to help manage the data in a library. RFID can help in the process of data input into the database library. The purpose of this study was to determine the performance of a library RFID system to help manage the data of the library activities. so that each activity such as borrowing and returning books in the library can be recorded accurately. The main components of this system are 13,56MHz RFID reader is used to read data from RFID tags that contain a primary key from the data book, RFID tag models sticker to be affixed to the collection of library books, Personal Computer (PC) to run the application system is already built, and modem for SMS Gateway features. System application are built using PHP programing language with Codeigniter framework and MySQL for the database. From the test result, the system has been run in accordance with the perlimenary draft. RFID reader can read tags on books accurately even in circumstances obstructed. RFID reader that is used has a limit of distance in reading the tag, which 3-4 cm. Input data into database is running well, and SMS Gateway features to schedule remainders return the books is going according to plan.